The State of Entrepreneurship and Innovativeness in Montenegro - Sanja Pekovic; Jelena Jovanovic; Zdravko Krivokapic; Aleksandar Vujovic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
European business sector pays an ever more increasing attention to competences such as sense of initiative and entrepreneurship but Western Balkan countries as transition countries from state regulated towards market economy, have a high level of resistance to private initiatives and entrepreneurship. The Erasmus REBUS project aims at developing, testing, validating and mainstreaming holistic and needs driven open learning modules to promote entrepreneurship competences of ICT and engineering graduates at the interface of academic education and learning in practical business contexts. University of Montenegro as partner on the Rebus project is involved in research about current situation of entrepreneurship and innovativeness in Montenegro. Accordingly, we performed research which consists three parts: Online questionnaires, Desk research and Interview. Target groups for the research are: students, HEI, enterprises, administration, Chamber of Commerce… In this paper are presented results of that research with special focus on results obtained in online questionnaires.
Keywords: L26; 330; entrepreneurship; innovation; desk research; questionnaire